The threat of state sponsored Cyber attacks in Canada: to serve and protect - MacDougall, Andrew (AUC Knowledge Fountain, 2015)
This Masters of Global Affairs project has been constructed for the use as a piece contributing to policy recommendations for the Canadian Federal government on their response to handling state-sponsored cyber attacks on critical national infrastructure (CNI) in Canada. Throughout this project an exploration is undertaken to understand the means of attacks that Canada has faced since the millennium, as well as to see what defense and security measures were of use, and what security measures were under-utilized. By exploring these attacks to Canada’s CNI, clarification on improvements for the federal government on its future state of cyber defense become available. This project will also look to shape policy recommendations that can be considered in further national security agenda creation as well as governmental policies affecting domestic, and global governance on cyber attacks.